EDUCATION THROUGH HEALTH PROGRAMMES: EFFORTS TO STRENGTHEN COMMUNITY HEALTH IN SUKMAJAYA VILLAGE, JOMBANG DISTRICT, CILEGON CITY - Ikhlasiah, Marthia; Mutmainnah, Inayatul; Hajar, Baiq Siti (TOPLAMA, 2024)
Objective study This is to provide service information education through health programmes: efforts to strengthen community health in Sukmajaya Village, Jombang District, Cilegon ty. As for the method used, i.e., ie The method used in this research is PAR (participatory action research). PAR is a research approach that actively involves all relevant parties in a participatory For study ongoing action. Results study that is In carrying out a health education programme in Sukmajaya Village, Jombang District, Cilegon City on November 13, 2023, it can be concluded that this effort has great potential to create even and sustainable positive changes in various aspects of community life. This programme not only educates about the importance of cleanliness for physical health but also has a significant impact on social and economic aspects. Through outreach sessions, practical demonstrations, and cross-sector collaboration, village communities are expected to understand and internalise good hygiene practices. This change in behaviour is not only temporary but is expected to become part of the norms and values that continue to be passed on from one generation to the next.